Integrity Management as Interorganizational Activity: Exploring Integrity Partnerships That Keep the Wheel in Motion. (2nd April 2016) - Hoekstra, Alain; Talsma, Jitse; Kaptein, Muel
Abstract : Much research on integrity management centers on the internal activities and measures individual organizations can employ to foster integrity. Using institutional and cultural theory, this article, conversely, explores how organizations can cooperate with peer organizations to manage integrity. Based on empirical research, 23 different integrity partnerships were mapped and analyzed, resulting in four categories: the integrity workshop (sharing instruments), the integrity pool (sharing capacity), the integrity forum (sharing knowledge), and the integrity megaphone (sharing influence). This categorization offers a first overview of existing forms of interorganizational cooperation in integrity management. It identifies the characteristics, practical benefits, and pitfalls of the four integrity partnership categories. It demonstrates that integrity management is not necessarily a "wheel" that organizations have to reinvent and keep in motion entirely on their own, and it provides a basis for future research in this underresearched area.